ОРГАНИЗАЦИЯ УПРАВЛЕНИЯ КРЕДИТНЫМИ РИСКАМИ В БАНКАХ ВТОРОГО УРОВНЯ (Journal of Economic Research & Business Administration, 2015)
Bank main objective is "the golden mean" finding, i.e. an optimum parity between degree of risk and profitableness on credit operations by means of competent management of credit risk that is realized by means of dialogue and the analysis of the basic ways of management by credit risk, working out of practical actions for decrease in risk of nonpayment under loans.